2018
DOI: 10.1007/978-3-319-64016-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Viva in Higher Education

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A cross-national (UK, South Africa, Hong Kong, US, Australia, and NZ) comparison of PhD supervision models, milestones, and examination procedures found that each country differed in terms of examination procedures and the role of the supervisor in the oral examination (Dobson, 2018;Dominguez-Whitehead & Maringe, 2020).…”
Section: Supervisors In Doctoral Oral Examinations: International Per...mentioning
confidence: 99%
See 3 more Smart Citations
“…A cross-national (UK, South Africa, Hong Kong, US, Australia, and NZ) comparison of PhD supervision models, milestones, and examination procedures found that each country differed in terms of examination procedures and the role of the supervisor in the oral examination (Dobson, 2018;Dominguez-Whitehead & Maringe, 2020).…”
Section: Supervisors In Doctoral Oral Examinations: International Per...mentioning
confidence: 99%
“…However, the supervisor does not have a veto vote regarding the final outcome. In Spain, supervisors may attend the oral defence as a member of the audience but are not allowed to participate in the discussion (Hobson, 2019).…”
Section: Supervisors In Doctoral Oral Examinations: International Per...mentioning
confidence: 99%
See 2 more Smart Citations
“…At a further meta-level, candidates could even join supervisors and examiners to check the sparse literature which, as a research theme in higher education, researches examining for vivas (Mullins & Kiley, 2002;Mežek & Swales, 2016;Dobson, 2018) or reviews oral exams in general (Jonghin, 2010). Also, consulting research articles which attempt a genre analysis of sections of doctoral theses might be helpful.…”
Section: Problems With Viva Preparationmentioning
confidence: 99%